Three-Dimensional Printing of a Polycaprolactone-Fluorapatite Nanocomposite Scaffold and Simulation of Its Mechanical Properties - Mojtaba Momeni; Kamran Amini; Ali Heidari; Mohammad Khodaei (Isfahan University of Medical Sciences, 2022)
The use of porous nanobiocomposite scaffolds for maxillofacial fractures and internal surface optimization of artificial grafts utilizing nanotechnology can improve cell adhesion, mechanical properties, and adsorption rate. Porous scaffolds have been the subject of numerous investigations, especiallyfor broken and damaged parts of the facial bone. The goal of this study was to look into the biological, experimental, and numerical study of the mechanical properties of porous scaffolds under static loading conditions.Materials & Methods:In this study, a bone scaffold of polycaprolactone-Fluorapatite (PCL / nFA) nanocomposite materials containing (0, 10, 20, 30 %wt.) Fluorapatite nanoparticles was designed and manufactured using a 3D printer with Fused Deposition Modelling (FDM) process. The scaffolds were designed in SolidWorks software with 70% porosity and then transferred to Abaqus software for simulation.Results:In addition, following 28 days of immersion in the simulated body fluid, the bioactivity test of pure and composite scaffolds showedthat the PCL /20nFA composite sample produced the most apatite on the surface. DAPI staining and fluorescent microscopy observation, confirm cell viability on the 3D printed scaffold.Conclusion:The Von Mises stress and compressive test simulations revealed that the porous scaffold model may be used for maxillofacial bone replacement and has good mechanical strength and stability.